Currency Futures Trading in India - Jaiswal, K. S.; Saha, Dipti (Indian Journal of Finance, 2009)
More than five decades of Indian economic planning and subsequent libralization had led the country to an esctatic phase of development. The development through disintermediation, deregulation, globalization and emergence of the vibrant capital market has contributed to the expansion of opportunities. As a result, capital market has emerged as a major contributor to the growth of foreign exchange reserves of the country. In fact, in the emerging world market, India has beaten several developing countries. In the post libralization era, the finance sector has witnessed a complete metamorphosis. Financial intermediaries abroad have created new varieties of instruments and transactions called Derivatives and risk management tools such as options, futures and swaps which are used to transform one or more properties of an asset or liability. Financial libralization has brought inherent risk, and as a result, corporate and institutional investors are looking towards derivatives for hedging the risk. Since the volume of international trade and capital flows are rising, more and more banks are exposed to various currencies and the emerging derivatives in foreign countries are increasingly used by banks to bring variations in the sensitivity of their funds and also the underlying portfolio.